Bank Syariah Di Indonesia: Ketaatan Pada Prinsip- Prinsip Syariah Dan Kesehatan Finansial - - Falikhatun; Yasmin Umar Assegaf (Conference In Business, Accounting, And Management (CBAM), 2012)
The objective of this paper is to examine the sharia principles implementation on the financial health in syariah banking in Indonesia. The study used 36 annual reports of listed companies on the website of syariah banking in Indonesia from 2007 – 2010. Sample was selected using purposive sampling method. While multiple regression analysis was used to test the hypotheses developed in this research. The result found that sharia principles (Islamic investment Ratio, Profit sharing Financiing ratio, Islamic Income ratio and Director’s – Employee Welfare Ratio) are positive significant to financial health. The contribution of this study is provided additional suggestion for regulator dan Islamic banking participant as the mechanism of hablum minnallah wa hablum minanaas.Keywords: sharia principles, financial health, banking